A rare case of pulmonary Mycobacterium szulgai treated with combined drug therapy and bilateral surgical lung resection. Issue 3 (3rd July 2018) - Hockmann, Karlo; Saint-Pierre, Mathieu D.; Moran-Mendoza, Onofre; Wobeser, Wendy; Neder, J. Alberto; Martinez-Cajas, Jorge L.; Evans, Gerald A.; Reid, Kenneth R.
ABSTRACT: Mycobacterium szulgai is an uncommonly isolated non-tuberculous mycobacterium (NTM) of clinical and pathological significance that is usually managed with antimycobacterial therapy alone. We describe an unusual case in a 52-year-old woman with mild dyspnea, productive cough and small-volume hemoptysis. Chest imaging demonstrated large bilateral apical lung cavities with positive bronchial washings for M. szulgai. Despite medical treatment the patient's symptoms did not resolve and repeat imaging revealed enlarging apical lung cavities. She was treated with bilateral upper lung resections in addition to continued antimicrobial therapy, with full resolution of symptoms and cavitary lesions one year after surgery. Our report is the first to show that bilateral lung resection, in addition to medical treatment, can be used successfully to eradicate bilateral cavitary pulmonary disease due to M. szulgai. RÉSUMÉ Mycobacterium szulgai est une mycobactérie non tuberculeuse (MNT) d'importance clinique et pathologique exceptionnellement isolée qui est habituellement prise en charge à l'aide d'un traitement antimycobactérien seul. Nous décrivons un cas inhabituel observé chez une femme de 52 ans souffrant de dyspnée légère, d'une toux productive et d'une hémoptysie de faible abondance. Les examens d'imagerie thoracique ont démontré l'existence de grandes cavités pulmonaires apicales bilatérales et des lavages bronchoalvéolaires ont révélé la présence de M. szulgai . Malgré le traitement médical, les symptômes de la patiente ne se sont pas résorbés et de nouveaux examens par imagerie ont révélé un agrandissement des cavités pulmonaires apicales. Elle a été traitée par résections du poumon supérieur, tout en poursuivant la thérapie antimicrobienne. Les symptômes et les lésions cavitaires se sont entièrement résorbés un an après la chirurgie. Notre rapport est le premier à démontrer que la résection pulmonaire bilatérale – en plus du traitement médical – peut être utilisée avec succès pour éradiquer la maladie pulmonaire cavitaire bilatérale attribuable à M. szulgai .